FL-ASB: A Fuzzy Logic Based Adaptive-period Single-hop Broadcast Protocol - Bin Pan; Hao Wu; Jin Wang (International Journal of Distributed Sensor Networks)
In vehicular ad hoc networks, vehicle-to-vehicle–based broadcast can fast disseminate safety messages between vehicles within the whole network and hence expand drivers perception vision, which will reduce the accident probability and ensure the transportation reliability. As for fixed-period single-hop broadcast protocol, disseminating safety messages frequently can cause excessive network load. However, increasing period purely does not guarantee the real-time performance. In addition, exiting adaptive-period single-hop broadcast protocols also have limitations without considering synthetically various impact factors. Thus, how to design a single-hop broadcast protocol that can dynamically adjust the broadcast period according to the actual road condition is a pressing issue. A Fuzzy Logic Based Adaptive-period Single-hop Broadcast Protocol in vehicular ad hoc networks is designed in this article, which provides a new solution for the dissemination of period safety messages. In this article, the impact of various factors (such as the number of one-hop neighbor nodes, vehicle speed, received signal strength index, and visibility) on the single-hop broadcast period has been analyzed. In view of each impact factor, we design corresponding membership function and fuzzy rules according to the specific scenarios and parameters. It realizes the adaptive changes of period safety messages broadcast period through the simulation of the proposed fuzzy logic inference system. Finally, we verify the performance of the Fuzzy Logic Based Adaptive-period Single-hop Broadcast Protocol in a bidirectional four-lane highway scenario. Simulation results show that the proposed Fuzzy Logic Based Adaptive-period Single-hop Broadcast Protocol has obvious advantages in terms of network load ratio, average one-hop delay, and delivery ratio.